2014
DOI: 10.5194/acp-14-9077-2014
|View full text |Cite
|
Sign up to set email alerts
|

Countergradient heat flux observations during the evening transition period

Abstract: Abstract. Gradient-based turbulence models generally assume that the buoyancy flux ceases to introduce heat into the surface layer of the atmospheric boundary layer in temporal consonance with the gradient of the local virtual potential temperature. Here, we hypothesize that during the evening transition a delay exists between the instant when the buoyancy flux goes to zero and the time when the local gradient of the virtual potential temperature indicates a sign change. This phenomenon is studied using a rang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…An average shear production for this group is about 0.7 as observed for the near-neutral data during the afternoon transition just before stable stratification has started. As discussed in Blay-Carreras et al (2014b), at this site, there is a delay period between when the buoyancy flux becomes zero and when the vertical virtual potential temperature gradient becomes zero. Therefore, this group of…”
Section: Normalization Of the Tke Budget Termsmentioning
confidence: 99%
“…An average shear production for this group is about 0.7 as observed for the near-neutral data during the afternoon transition just before stable stratification has started. As discussed in Blay-Carreras et al (2014b), at this site, there is a delay period between when the buoyancy flux becomes zero and when the vertical virtual potential temperature gradient becomes zero. Therefore, this group of…”
Section: Normalization Of the Tke Budget Termsmentioning
confidence: 99%
“…7a), when the heat flux at the same level has already become downward. Blay-Carreras et al (2014) reported on a sensible heat flux switching sign before the vertical temperature gradient switched sign near the surface, indicating the occurrence of countergradient heat fluxes at those levels. This phenomenon can be investigated with the present data in great detail by looking at individual cases.…”
Section: The Effect Of the Power Plant On The Local Atmospheric Boundmentioning
confidence: 99%
“…Generally, stratification begins to develop as soon as the sensible heat flux reverses to downward. In contrast, Blay-Carreras et al (2014) and Sandeep et al (2015) find that the surface inversion did not begin to develop until about 30 min after the sensible heat flux reversed sign, possibly due to the lingering influence of large convective eddies.…”
Section: Temperature Decrease Near the Surfacementioning
confidence: 84%